O-GLCNACASE (OGA) INHIBITOR COMBINATION THERAPY - NUTHALL, Hugh N; FLEISHER, Adam S; BIGLAN, Kevin; MERGOTT, Dustin James (2024)
The present invention provides methods of slowing progression of, treating, and/or preventing a disease characterized by amyloid beta deposits and/or a disease characterized by amyloid beta deposits and aberrant tau aggregation. Such methods comprise administering to a patient in need of such treatment an effective amount of an anti-N3pG Aβ antibody and an effective amount of an OGA inhibitor.